Empowering Family Physicians to Impart Proper Inhaler Teaching to Patients with Chronic Obstructive Pulmonary Disease and Asthma - Janice M Leung; Mohit Bhutani; Richard Leigh; Dan Pelletier; Cathy Good; Don D Sin (Canadian Respiratory Journal)
BACKGROUND: Patients with chronic obstructive pulmonary disease (COPD) and asthma depend on inhalers for management, but critical errors committed during inhaler use can limit drug effectiveness. Outpatient education in inhaler technique remains inconsistent due to limited resources and inadequate provider knowledge.